COMPUTER SIMULATION OF RIDE DYNAMICS AND WEAR OF THE WHEELS OF THE FREIGHT LOCOMOTIVE WITH RADIAL INSTALLATION OF THE WHEEL PAIRS - Mikhalchenko, H. S.; Yazykov, V. M.; Kossov, V. S.; Spirov, O. V. (Science and Transport Progress, 2004)
Results of detailed simulation of motion of the freight locomotive equipped with original three axle bogies with the radial steering mechanism designed by VNIKTI are given. The simulation was performed with the help of the program UM Loco developed at BSTU. To solve the wheel-rail contact problem an approximate model which does not lead to stiff equations of motion and can be used for non-elliptical contact areas was used.